Clinical usefulness of esophagogastric junction distensibility measurement in patients with achalasia before and after peroral endoscopic myotomy - Chang, Junsu; Yoo, In kyung; Günay, Süleyman; Paköz, Zehra Betül; Cho, Joo young (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The aim of this study was to determine the clinical efficacy of measuring the esophagogastric junction (EGJ) distensibility index in patients with achalasia before and after peroral endoscopic myotomy (POEM). Materials and Methods: Retrospective data were collected from 195 patients who underwent POEM from November 2014 to November 2017 at our clinic. The Eckardt score, high-resolution manometry (HRM), and esophagogastric junction (EGJ) distensibility were measured before and 6 months after POEM. Treatment failure was defined as a post-procedure Eckardt score >3 or patients who underwent repeat POEM. Results: Distensibility index (DI, mm2/mmHg) before and after POEM was 3.42±3.55 and 11.57±6.64, respectively (p <0.01). There was no difference in DI between achalasia subtypes, I,II,III, respectively (11.45±6.24 vs. 15.49±11.53 vs. 13.27±9.49, p=0.22) or previous treatment history (15.39±10.85 vs. 11.10±7.25, p=0.20). DI was higher in patients with reflux esophagitis after POEM, but the difference was no significant (13.59±7.15 vs. 12.54±10.9, p=0.571). Conclusion: This study showed that EGJ distensibility measurement is useful to assess post-POEM outcomes. These findings suggest that the functional lumen imaging probe (FLIP) may be a useful method for assessing clinical efficacy of POEM in patients with achalasia. However this is a costly procedure that requires experience.